Affective teachable agent in virtual learning environment - Borjigin, Ailiya (2014)
Teachable Agent (TA) is a special type of pedagogical agent which instantiates the educational theory of “Learning-by-Teaching”. Soon after its emergence, research of TA becomes an active field, as it can solve the over-scaffolded problem in traditional pedagogical systems, and encourage students to take the responsibility of learning. Apart from the benefits, existing TA design also has limitations. One is the lack of enough proactive interactions with students during the learning process, and the other is the lack of believability to arouse student’s empathy so as to offer students an immersive learning experience.